Food Acquisition in the Geography of Brazilian Obesity - Alves, Camila Elisa; Dal' Magro, Glenio Piran; Viacava, Keitiline R.; Dewes, Homero (Frontiers in Public Health, 2020)
Overweight and obesity are a worldwide pandemic with geographic differences. Possible explanations include variable access to food and its quality, dietary habits of the populations, behavioral patterns, and characteristics of the food markets. This study aimed to examine the acquisition of food in the different regions of Brazil and to relate it with the geography of Brazilian obesity. We used data provided by a Brazilian official organ, which gathers periodic data on the household food acquisition. Descriptive statistics and multidimensional scaling techniques were used to ascertain the similarity of food acquisition among populations in the Brazilian states. High levels of overweight and obesity occur in all states (>44%), especially in the southern half of the country (>54%). We found differences in the food acquisition patterns throughout the country. Furthermore, we identify that states with similar dietary patterns have similar population levels of overweight and obesity, demonstrating a possible relationship between the food supply models and these food insecurity manifestations as expressed in the individual health. However, the occurrence of regional singularities suggests that the food supply model constitutes only one of the multiple variables that compete for diversity in the Brazilian regional distribution of obesity and overweight. We found that socioeconomic conditions influence nutritional misalignment in the geography of Brazil. Our results show that overweight and obesity have a higher occurrence in middle age (35–79 years), and it is more present in females. Moreover, women with lower education and lower incomes have higher levels of overweight and obesity, an association of unhealthy food intake with poverty. In men, obesity is more frequent in those with more schooling and higher incomes. Based on the widely variable geographical characteristics of the distant states of Brazil, we conclude that overweight and obesity go beyond an individual lifestyle and access to quality food, and is more related to a complex framing of factors, like schooling, age, sex, income, feeding patterns, food markets, and anthropological circumstances.